Pengaruh Customer Online Rating Dan Review Terhadap Keputusan Pembelian Pada Pengguna Marketplace Tokopedia (Studi Kasus PadaMahasiswa Universitas Muhammadiyah Metro) - Marilyn, Regiana; Lelawati, Nina (Jurnal Manajemen DIVERSIFIKASI, 2023)
The author gives the title thesis "The Influence of Online Customer Ratings and Reviews on Purchase Decisions for Tokopedia Marketplace Users, (Case Study on Muhammadiyah Metro University Students). This research was conducted in order to determine the effect of online customer ratings and reviews on purchasing decisions on Tokopedia marketplace users at Muhammadiyah Metro University students. The type of research used is quantitative research with a population of 5,743 students. Sampling technique using Accidental Sampling. Only 98 samples used were in accordance with predetermined criteria. The data used is primary data with the distribution of questionnaires in the form of a list of questions with several alternative answers for respondents. The statistical test used to test the hypothesis was multiple linear regression analysis and was tested using the statistical packages for the social science (SPSS) version 25 program. Based on the results of statistical tests, it shows that online customer ratings and reviews have a positive or significant influence on the purchasing decisions of Tokopedia marketplace users for Muhammadiyah Metro University students. Based on the results of statistical tests, it shows that online customer ratings and reviews have a positive or significant influence on the purchasing decisions of Tokopedia marketplace users for Muhammadiyah Metro University students.